Finite Element Model for Pull-Out Test of Reinforcement Embedded in Confined Concrete - Sulaiman, Muhd Fauzy; Ma, Chau-Khun; Mohd Apandi, Nazirah; Chin, Chee-Loong; Ler, Kee-Hong (International Journal of Integrated Engineering, 2025)
A finite element (FE) model was developed to simulate the pull-out test of steel rebar embedded in concrete confined with pre-tensioned steel straps. The model treated both the concrete and steel rebars as refined solid elements, enabling explicit representation of their deformations. A surface-to-surface contact model was employed at the concrete-rebar interface to ensure accurate load transfer. The importance of using a confined concrete model capable of accurately simulating nonlinear behavior under high confining pressures was emphasized in the modelling process. For this purpose, the concrete damaged-plasticity (CDP) model was adopted. Multiple pull-out tests were simulated using this approach, and comparisons with experimental data demonstrated that the proposed FE model accurately reproduced bond stress-slip responses. Additionally, the model successfully captured different failure modes, including splitting failure in specimens without confinement and pull-out failure in confined specimens.